Transcriptome analysis reveals rice MADS13 as an important repressor of the carpel development pathway in ovules. (9th October 2020) - Osnato, Michela; Lacchini, Elia; Pilatone, Alessandro; Dreni, Ludovico; Grioni, Andrea; Chiara, Matteo; Horner, David; Pelaz, Soraya; Kater, Martin M
Abstract: In angiosperms, floral homeotic genes encoding MADS-domain transcription factors regulate the development of floral organs. Specifically, members of the SEPALLATA (SEP) and AGAMOUS (AG) subfamilies form higher-order protein complexes to control floral meristem determinacy and to specify the identity of female reproductive organs. In rice, the AG subfamily gene OsMADS13 is intimately involved in the determination of ovule identity, since knock-out mutant plants develop carpel-like structures in place of ovules, resulting in female sterility. Little is known about the regulatory pathways at the base of rice gynoecium development. To investigate molecular mechanisms acting downstream of OsMADS13, we obtained transcriptomes of immature inflorescences from wild-type and Osmads13 mutant plants. Among a total of 476 differentially expressed genes (DEGs), a substantial overlap with DEGs from the SEP -family Osmads1 mutant was found, suggesting that OsMADS1 and OsMADS13 may act on a common set of target genes. Expression studies and preliminary analyses of two up-regulated genes encoding Zinc-finger transcription factors indicated that our dataset represents a valuable resource for the identification of both OsMADS13 target genes and novel players in rice ovule development. Taken together, our study suggests that OsMADS13 is an important repressor of the carpel pathway during ovule development. Abstract : Transcriptomic analysis of immature inflorescences from rice Osmads13 mutant plants indicates that OsMADS13 is an important repressor of the carpel pathway during ovule development.